Male love : a problem in Greek ethics : and other writings - Symonds, John Addington; Peters, Robert; Lauritsen, John (New York : Pagan Press, 1983)
Fonds Suzan Daniel (FSD)
Bevat volgende teksten van John Addington Symonds: 'A problem in Greek ethics', 'A problem in modern ethics', 'Studies of the Greek poets' en brieven.
Engels
Monografie